Indonesian English Teachers’ Social-Emotional Competence and Students’ English Learning Motivation - Larasati Anisa; Lingga Agustina Suganda; Hariswan Putera Jaya (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
This study was carried out to determine the correlation between the social-emotional competence of the English teachers and the English learning motivation of their students. The sample  was 111 students of secondary school. This study provides not only the correlation but also the survey results of teachers’ social-emotional competence and students learning motivation as well as the contribution of the teachers’ competence to their students’ motivation. The instruments used in this study were two questionnaires that were given to the students to assess their learning motivation and the social-emotional competence of their English teachers. The results of the study presented that there was a fairly significant correlation between the two variables, with teachers’ social-emotional competence contributing 23.1% to students’ learning motivation. The results also showed that the self-management of teachers’ social-emotional competence gave the highest contribution to students’ motivation with 16.8% contribution value while the self-awareness gave the lowest contribution with 3.8%.